2019
DOI: 10.1002/pc.25337
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of a compatible wood‐plastic composite prepared by using poly(butylene succinate)‐based polyurethane prepolymer

Abstract: Wood‐plastic composites (WPCs) are sustainable green material with extensive application prospects in both industry and daily life. So a more convenient, environmentally friendly and effective method is crucial. In this work, WPC was composed by 60 wt% poly(butylene succinate) (PBS) matrix, 10 wt% compatibilizer, and 30 wt% wood flour (WF) through extruder and injection machine. The effects of PBS diol‐based polyurethane prepolymer (PBSPUP) compatibilizer on the structure and properties of WPCs were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
(42 reference statements)
0
18
0
Order By: Relevance
“…Compared to our previous gel permeation chromatography test, it can be concluded that the synthesis of PCLPU and TPUP was successful. The IR spectra of the different PCL‐CS composites are shown in Figure , it can be seen that apart from PS‐0, all the other composites (i.e., PSTI‐3, PSPU‐2, PSDI‐2, PSPI‐1, and PSTP‐0) exhibited a main peak with maximum absorbance of about 3480 cm −1 corresponding to the N─H of urethane moieties . Interestingly, the typical absorption peak of ─NCO (around 2270 cm −1 ) in PI, MDI, MTI, and PCLPU disappeared suggesting that the ─NCO groups were consumed during the formation of the urethane bond.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Compared to our previous gel permeation chromatography test, it can be concluded that the synthesis of PCLPU and TPUP was successful. The IR spectra of the different PCL‐CS composites are shown in Figure , it can be seen that apart from PS‐0, all the other composites (i.e., PSTI‐3, PSPU‐2, PSDI‐2, PSPI‐1, and PSTP‐0) exhibited a main peak with maximum absorbance of about 3480 cm −1 corresponding to the N─H of urethane moieties . Interestingly, the typical absorption peak of ─NCO (around 2270 cm −1 ) in PI, MDI, MTI, and PCLPU disappeared suggesting that the ─NCO groups were consumed during the formation of the urethane bond.…”
Section: Resultsmentioning
confidence: 98%
“…Synthesis of polycaprolactone diol based polyurethane pre‐polymer (PCLPU) has been reported in our earlier works . The specific reaction steps for preparing PCLPU and ─NCO‐terminated polyurethane pre‐polymer (TPUP) can be found in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, water molecules can easily overcome the resistance to contact the hydroxyl group of WF, resulting in a higher water absorption rate. [21,23] For the WUF system, the abundant hydrophilic groups in the system make it easy to interact with water molecules, so the water absorption rate of WUF is naturally high, can verified by its contact angle result.…”
Section: Resultsmentioning
confidence: 99%
“…The figure shows the FTIR spectra of starch/PBAT composite film doped with different content of lignin. As shown in Figure 1, the four groups of starch/PBAT composite materials all have an absorption peak at 1518 cm −1 , which is attributed to the presence of N-H in the urethane bond of the urethane [19]. Moreover, the absorption peaks at 1738 cm −1 and 1267 cm −1 are due to the stretching vibration of the C-O and C=O group pairs in the urethane [19,20].…”
Section: Infrared Results Of Composite Materials With Ligninmentioning
confidence: 99%